Electrocatalytic hydrogen evolution mediated by an organotelluroxane macrocycle stabilized through secondary interactions - Narsimhulu, Gujju; Samuel, Calvin; Palani, Sathishkumar; Dasari, Sai Hemant Kumar; Krishnamoorthy, Kothandam; Baskar, Viswanathan (Dalton Transaction, 2023)
A discrete liphophilic organotelluroxane macrocycle has been found to catalyse the hydrogen evolution reaction (HER) by proton reduction efficiently. The macrocycle is synthesized via chloride abstraction from bis(p-methoxyphenyl) tellurium dichloride (p-MeOC6H5)2TeCl2 (1) by silver salts AgMX4 (MX4 = BF4-, and ClO4-) resulting in in situ generated di-cationic tetraorganoditelluroxane units; two such units are held together by two weak anions mu 2-MX4, bridging to form 12-membered di-cationic macrocycles [((p-MeO-C6H4)2Te)2(mu-O)(mu 2-F2BF2)2]2+ (2) and [((p-MeO-C6H4)2Te)2(mu-O)(mu 2-O2ClO2)2]2+ (3) stabilized via Te-(mu 2-BF4/ClO4), with secondary interactions. The charge is balanced by the presence of two more anions, one above and another below the plane of the macrocycle. Similar reaction at higher temperatures leads to the formation of telluronium salts R3TeX [X = BF4- (4), ClO4- (5)] as a major product. The BF4- anion containing macrocycle and telluronium salt were monitored using 19F NMR. HRMS confirmed the structural stability of all the compounds in the solution state. The organotelluroxane macrocycle 2 has been found to act as an efficient electrocatalyst for proton reduction in an organic medium in the presence of p-toluene sulfonic acid as a protic source. A discrete liphophilic organotelluroxane macrocycle has been found to catalyse hydrogen evolution reaction (HER) by proton reduction efficiently.
Keywords: Anion Transport; Proton-Reduction

Linear polymer comprising dual functionalities with hierarchical pores for lithium ion batteries - Aher, Jagadish D.; Palani, Sathishkumar; Krishnamoorthy, Kothandam (Chemelectrochem, 2023)
Organic materials with carbonyl, azo, nitrile and imine moieties are widely used in lithium batteries. The solubility of these materials in battery electrolytes is an issue. Aggregation of the organic molecules can suppress the solubility, but the accessibility of lithium-ion is hindered. Therefore, insoluble porous organic materials are desired. Herein, we synthesized a linear polymer with carbonyl and azo functionalities. Due to the presence of easily isomerizable azo moiety, a porous polymer was obtained. The polymer showed nano and micropores. The battery with the porous polymer showed an impressive specific capacity of 400 mA h/g at 0.2 A/g. If the battery is pre-conditioned, the specific capacity increased to 615 mA h/g at the same current density. The post-mortem analysis of the battery confirmed that the polymer didn't dissolve in the battery electrolyte. The control material is a small molecule with carbonyl and azo moieties that showed a poor specific capacity of 40 mA h/g indicating the necessity to have a hierarchically porous dual-functional polymer. Polymers for batteries: A linear polymer with micro and Nano pores with azo and carbonyl functionalities renders increased accessibility to Li ions after preconditioning. During charge-discharge experiment Azo-Carb-PDI electrode had impressive discharge capacity of 469 mA h/g after 500 cycle which is almost 15 times higher than the monomer (Azo-PDI-Azo, 30 mA h/g after 100 cycle).image
Keywords: azo polymer; carbonyl; Li-ion battery; porous polymer; Rylene-imide

Shuttle balance between lithiophilic functionalities substituted on conjugated polymers to improve lithium-ion diffusion and cycling stability of batteries - Kargude, Radhakisan; Javaregowda, Bharathkumar H.; Palani, Sathishkumar; Singh, Anup K.; Krishnamoorthy, Kothandam (Macromolecules, 2024)
Herein, we report the design and synthesis of i-Indigo and trans-1,2-di(2-thienyl)ethylene (TVT) comprising copolymers with various side chains that are used as anode-cum-binder in Li-ion batteries. The TVT disrupts the crystallinity, and the i-Indigo renders the handle for unsymmetrical substitution. Polymer P1 comprises alkyl chains on i-Indigo, whereas P2 comprises an alkyl chain and a chain with a urethane moiety as another side chain. Polymer P3 comprises i-Indigo with a urethane moiety and triethylene glycol as side chains. The i-Indigo in P4 is substituted with triethylene glycol and alkyl chains as side chains. These polymers were found to be amorphous with pi-pi stacking due to the extremely small torsional angle imparted by TVT moieties. All of these polymers showed comparable specific capacity while used as an anode in Li-ion batteries due to the presence of a common conjugated backbone. However, the battery metrics varied significantly while the current density of the batteries varied between 0.1 and 2.0 A g(-1). P1 and P2 showed a very close recovery of specific capacity at 0.1 A g(-1) before and after various current densities. However, polymers P3 and P4 did not recover from the specific capacity fading due to the presence of triethylene glycol side chain that degraded. Polymer P2 with an alkyl side chain and a chain with a urethane moiety showed stable performance over 2000 charge-discharge cycles. Contrary to this, the stability of polymers with triethylene glycol side chains decreased over 2000 charge-discharge cycles. Polymer P2 with a urethane side chain also showed improved Li-ion diffusion because the urethane moiety facilitated better Li-ion transport.